1978
DOI: 10.1136/bjo.62.8.509
|View full text |Cite
|
Sign up to set email alerts
|

Antichlamydial antibody in tears and sera, and serotypes of Chlamydia trachomatis isolated from schoolchildren in Southern Tunisia.

Abstract: (Wang and Grayston, 1970;Treharne et al., 1971) has greatly facilitated the study of the TRIC agents responsible for hyperendemic trachoma of eye-to-eye transmission, and the TRIC agents of paratrachoma (both ocular and genital) of sexual transmission, with occasional transfer to the eye (Jones, 1975;Treharne et al., 1977).The microimmunofluorescence method has also been applied to the measurement of type-specific antichlamydial antibody in serum (Dwyer et al

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

1982
1982
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…Their proposal was based on the finding of a high prevalence of antichlamydial IgG antibody in ocular secretions from children with active trachoma, and the fact that higher titres of antichlamydial IgG antibody were found in serum and tears from isolation positive than isolation negative subjects [10][11][12]. On the other hand, ocular secretions from children with trachoma showed neutralizing activity in the owl monkey model [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their proposal was based on the finding of a high prevalence of antichlamydial IgG antibody in ocular secretions from children with active trachoma, and the fact that higher titres of antichlamydial IgG antibody were found in serum and tears from isolation positive than isolation negative subjects [10][11][12]. On the other hand, ocular secretions from children with trachoma showed neutralizing activity in the owl monkey model [8].…”
Section: Discussionmentioning
confidence: 99%
“…Barenfanger demonstrated that neutralization was mediated in this case by immunoglobulin [9]. Others have found a positive correlation between anti-chlamydial antibody levels and the presence of chlamydia in the conjunctiva of individuals in trachoma endemic communities; indeed the presence of such antibodies has been used as a diagnostic marker of active trachoma [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Reinfection with a different serovar tends to raise antibody responses to the previous serovar (20). There is no evidence that tear antibodies confer protection against chlamydial infection (21,22). Byrne and Krueger have shown that gamma interferon inhibits chlamydial growth and viability in cell cultures and probably serves as one host defense mechanism (23).…”
Section: Immunitymentioning
confidence: 99%
“…Studies of tear immunglobulins using the same animal model, however, revealed a change by three weeks after infection from a predominance of IgM to either IgG or IgA [10]. Antichlamydial IgG and IgA were also the predominant immunoglobulin types (with levels of IgG greater than those of IgA) detected in the tears of patients with active trachoma [11,12]. In the present study, IgG and IgA, with small amounts of IgM, were also found in the subepithelial conjunctival tissue and occasionally IgG and IgA were seen on the epithelial surface.…”
Section: Discussionmentioning
confidence: 99%